2022
DOI: 10.1002/alz.12644
|View full text |Cite
|
Sign up to set email alerts
|

Changes in cognitive functioning after COVID‐19: A systematic review and meta‐analysis

Abstract: Introduction:We conducted a systematic review and meta-analysis of the cognitive effects of coronavirus disease 2019 (COVID-19) in adults with no prior history of cognitive impairment. Methods: Searches in Medline/Web of Science/Embase from January 1, 2020, to December 13, 2021, were performed following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. A meta-analysis of the Montreal Cognitive Assessment (MoCA) total score comparing recovered COVID-19 and healthy controls … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
169
1
15

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 217 publications
(194 citation statements)
references
References 53 publications
9
169
1
15
Order By: Relevance
“…Moreover, whilst disease severity was associated with reduced lung function, there was no association between disease severity or lung function with mild cognitive decline, suggesting that symptoms of acute COVID-19 infection are not necessarily associated with cognitive function in the months following COVID-19 infection. Our finding of no association between CI and disease severity including respiratory function is in keeping with other studies (Table S1) 2 . This finding has major public health and economic implications: relying on disease severity (especially mild to moderate distinction) to estimate disease burden will result in a significant underestimate.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Moreover, whilst disease severity was associated with reduced lung function, there was no association between disease severity or lung function with mild cognitive decline, suggesting that symptoms of acute COVID-19 infection are not necessarily associated with cognitive function in the months following COVID-19 infection. Our finding of no association between CI and disease severity including respiratory function is in keeping with other studies (Table S1) 2 . This finding has major public health and economic implications: relying on disease severity (especially mild to moderate distinction) to estimate disease burden will result in a significant underestimate.…”
Section: Discussionsupporting
confidence: 93%
“…QUIN > 605 (nM): reference 32 The continous outcomes provide the best model (see panel A). 2 . KYN (uM) /TRP (uM) ratio * 10 3 (standard cut-off >63): reference 33 .…”
Section: Panel Bmentioning
confidence: 99%
See 1 more Smart Citation
“…id=2448b930-1451-43e4-8634-c0c16707c749; last accessed 27 May 2022; Kallet et al, 2019;Lee et al, 2021;Zuin et al, 2021;Stefanou et al, 2022;Visco et al, 2022). It has been observed that about ∼75% of hospitalized COVID-19 patients have at least one COVID-19-associated comorbidity and COVID-19 patients with underlying chronic illnesses are more likely be affected with a more adverse and unfavorable prognosis (Chiner-Vives et al, 2022;Crivelli et al, 2022;Kirtipal et al, 2022).…”
Section: Sars-cov-2 -The Short-and Long-term Neurological Sequelaementioning
confidence: 99%
“…For this reason, researches into the putative link between SARS-CoV-2 and neurological manifestations continue to grow (Desai et al, 2021; Ghannam et al, 2020; Guadarrama-Ortiz et al, 2020). Cognitive dysfunction, also known as brain fog, is defined as the decrements in the cognitive status during continuous mental activity (García-Sánchez et al, 2022). Brain fog as a general term can present as confusion, difficulty finding the appropriate words, disorientation, memory problems, altered mental status, and trouble concentrating (Altuna et al, 2021; Asadi-Pooya et al, 2022; Hampshire et al, 2021).…”
Section: Introductionmentioning
confidence: 99%